Hubungan Pelayanan Kesehatan terhadap Tingkat Kepuasan Pasien - Sapwal, Muh. Jumaidi; Khairari, Nandang DD; Arroniri, Khaerul Warisin (ProHealth Journal, 2024)
Nurses are the most health workers (47.28%) in Indonesia, the largest in each region with a total of 46.84% working in health centers and are leading health workers who provide health services to the community every day, so that the performance of nurses also determines the overall success of health centers in achieving their programs. The success of health services at the Health Center is highly determined by the performance of the nurses, dissatisfaction or disappointment of the patient will arise if the performance of the health services he gets is not in accordance with his expectations. For this reason, it is necessary to know the relationship between health services and the level of patient satisfaction at the Dasan Lekong Health Center. This research method is quantitatively correlated with a cross sectional approach. The total inpatient and outpatient population is 60 people based on visits in August-October 2023, the sampling technique uses total sampling, namely sampling is equal to the number of population. The research instrument used a questionnaire. This study shows that most of the health services at the Dasan Lekong Health Center are in the good category, namely 34 (56.7%). Meanwhile, the level of satisfaction is in the satisfied category, which is 25 (41.7%). The results of the statistical test using spearman rank obtained a p-value of 0.000 which means a p-value of < α (0.05). This study can be concluded that there is a relationship between service and patient satisfaction at the Dasan Lekong Health Center